2019
DOI: 10.4236/sn.2019.84010
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Use and Empathy: A Mini Meta-Analysis

Abstract: Concerns about the effects of social media or social networking site (SNS) use on prosocial development are increasing. The aim of the current study is to meta-analytically summarize the research to date (k = 5) about the relationship between general SNS use and two components of empathy (i.e., empathic concern and perspective-taking). Random effects meta-analyses showed that SNS use was significantly and positively related to affective empathy though only marginally related to cognitive empathy. These effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
1
4
1
3
Order By: Relevance
“…These findings suggest that concerns about children's digital or screen media use are perhaps overblown in terms of impeding emotional skill development. In contrast to some previous findings that EI associated with some problematic media usage (Parker et al, 2008) and empathy associated with social media use (e.g., Guan et al, 2019), no screen or digital media use variable in this study related to child EI, empathy, or emotional regulation, though reading did associate with higher EI. Given the correlational nature of the data, we cannot know whether reading promotes EI or whether those high in EI enjoy reading.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings suggest that concerns about children's digital or screen media use are perhaps overblown in terms of impeding emotional skill development. In contrast to some previous findings that EI associated with some problematic media usage (Parker et al, 2008) and empathy associated with social media use (e.g., Guan et al, 2019), no screen or digital media use variable in this study related to child EI, empathy, or emotional regulation, though reading did associate with higher EI. Given the correlational nature of the data, we cannot know whether reading promotes EI or whether those high in EI enjoy reading.…”
Section: Discussioncontrasting
confidence: 99%
“…Further, in light of dropping empathy rates among US college students over a 30-year period (1979Konrath et al, 2011), some have argued that the concomitant rise in social media use is to blame, distracting from and displacing the more human connection derived from face-to-face interaction (Turkle, 2011; see also Chopik et al, 2017). However, casting doubt on this assertion, recent longitudinal evidence among 10-14-year-olds and 17-19-year-olds has revealed that time spent on social media positively predicted self-reported empathy over a one year (Vossen & Valkenburg, 2016) and three-year period (Stockdale & Coyne, 2020; see also Guan et al, 2019). Such findings likely stem from the affordances of media platforms that allow for reflection on both the content consumed and one's reaction to it.…”
Section: Media Use and Emotional Skillsmentioning
confidence: 99%
“…Our sample size of 1,253 was sensitive to effects of r = ±.06 with 80% power (α = .05, two-tailed). This means our study should be able to detect correlations higher than r = .06 or lower than −.06, a size comparable to previously reported average effect sizes ( r = .05–.07; Guan et al, 2019).…”
Section: Methodssupporting
confidence: 89%
“…We next conducted a mixed effects meta-analysis using the Comprehensive Meta-Analysis V3 software to combine the empathy results from our current study with those included in Guan et al,’s (2019) meta-analysis of five studies. This analysis calculated the weighted mean correlation between emotional empathy and social media use and also the weighted mean correlation between cognitive empathy and social media use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation